Effect of Microwave Disinfection on Compressive and Tensile Strengths of Dental Stones - Mahmood Robati Anaraki; Elnaz Moslehifard; Soran Aminifar; Hamed Ghanati (Tabriz University of Medical Sciences, 2013)
Background and aims. Although microwave irradiation has been used for disinfection of dental stone casts, there are concerns regarding mechanical damage to casts during the process. The aim of this study was to evaluate the effect of microwave irradiation on the compressive strength (CS) and diametral tensile strength (DTS) of stone casts. Materials and methods. In this in vitro study, 80 cylindrical type III and IV stone models (20 × 40 mm) were prepared and divided into 8 groups of 10. The DTS and CS of the specimens were measured by a mechanical testing machine at a crosshead speed of 0.5 cm/min after 7 times of frequent wetting, irradiating at an energy level of 600 W for 3 minutes and cooling. Data were analyzed by Student's t-test. Results. Microwave irradiation significantly increased DTS of type III and IV to 5.23 ± 0.64 and 8.17 ± 0.94, respectively (P < 0.01). Conclusion. According to the results, microwave disinfection increases DTS of type III and IV stone casts without any effects on their CS.